1996
DOI: 10.1523/jneurosci.16-12-03817.1996
|View full text |Cite
|
Sign up to set email alerts
|

The Taste of Monosodium Glutamate: Membrane Receptors in Taste Buds

Abstract: Receptor proteins for photoreception have been studied for several decades. More recently, putative receptors for olfaction have been isolated and characterized. In contrast, no receptors for taste have been identified yet by molecular cloning. This report describes experiments aimed at identifying a receptor responsible for the taste of monosodium glutamate (MSG). Using reverse transcriptase (IV)-PCR, we found that several ionotropic glutamate receptors are present in rat lingual tissues. However, these recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
175
1
8

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(189 citation statements)
references
References 64 publications
5
175
1
8
Order By: Relevance
“…The sensory innervation of the tongue is particularly interesting because it plays a major role not only in taste perceptions of sweet, sour, salt, bitter or umami (ASTBACK et al, 1995;CHAUDHARI et al, 1996), but also in information about the temperature and consistency of the food or drink. The PGP 9.5 immunoreactive nerve fibers supplying taste buds demonstrated in the present study would generally seem to represent the afferent innervation for those sensations.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The sensory innervation of the tongue is particularly interesting because it plays a major role not only in taste perceptions of sweet, sour, salt, bitter or umami (ASTBACK et al, 1995;CHAUDHARI et al, 1996), but also in information about the temperature and consistency of the food or drink. The PGP 9.5 immunoreactive nerve fibers supplying taste buds demonstrated in the present study would generally seem to represent the afferent innervation for those sensations.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Chaudhari et al [93,94] identified a truncated N-terminal version of mGluR4 in rat taste buds and showed that Chinese hamster ovary (CHO) cells expressing this receptor responded to L-glutamate in a concentration range appropriate for umami taste. Yang et al [95] showed by ISH that mGluR4 was expressed in a subset of rat taste bud cells.…”
Section: T2rs Are Gpc Receptors For Bitter Tastementioning
confidence: 99%
“…Many tissues demonstrate Glu, GluR and GluTPs, including but not limited to, CNS 122 , autonomic and sensory ganglia 123 , peripheral nerves-myelinated and unmyelinated 124,125 , vagus and other cholinergic nerves 124 , tachykinin containing sensory nerves and vestibular tissues 1 2 6 , 1 2 7 retinal photoreceptors 1 2 8 -1 3 0 , Muller cells 1 2 8 , 1 3 1 , adrenal medulla 123,133 , pituitary 134 , pineal gland 135 , endocrine pancreas [136][137][138][139][140][141][142][143][144][145][146][147] , immune system 148 , taste buds 149,150 , esophagus 151 , gut 70,100,[152][153][154] , ileal longitudinal muscle [155][156][157] , h e pa to c yt e s 6 8 , 1 5 8 , k i d n e y , s p l e e n s , o v a r i e s 4 8 , 1 5 9 , lungs 60,99,145,148,154,[158][159][160][161][162][163][164][165] , heart …”
Section: ) Glutamatementioning
confidence: 99%